Novel Type I/II Carbazole/Benzindole Photosensitizers Achieve Chemo-Photodynamic Synergistic Therapy for Suppressing Solid Tumors and Drug-Resistant Bacterial Infections - Zihao Wang; Xiao Liu; Yifan Ma; Jiaxin Zheng; Ke Xu; Yingxue Chang; Zhaoyan Ye; Yong Ling; Lei Wang (Molecules)
To address the clinical challenges posed by symbiotic drug-resistant bacterial infections and tumor microenvironments, this study designed and synthesized novel carbazole/benzindole-based photosensitizers A1–A4, systematically evaluating their antitumor and antibacterial therapeutic potential through chemo-photodynamic therapy. Especially, compound A4 demonstrated potent Type I/II reactive oxygen species (ROS) generation capabilities. In vitro experiments revealed that A4 concentration-dependently inhibited HT-29 cells under hypoxic conditions (IC50 = 0.89 μM) with a prominent photodynamic index (PI > 9.23), and substantially promoted cancer cell programmed death. In antibacterial evaluations, A4 achieved the complete eradication of dermal MRSA infections within 7 days through ROS-mediated membrane disruption under illumination. In the HT-29 xenograft model, the PDT–chemotherapy synergy strategy achieved a tumor suppression rate of 96%. This work establishes an innovative strategy for the combinatorial management of multidrug-resistant infections and solid tumors.